Liquidity Provision with Limit Orders and a Strategic Specialist - Seppi, Duane J. (Review of Financial Studies, 1997)
Journal Article Liquidity Provision with Limit Orders and a Strategic Specialist Get access Duane J. Seppi Duane J. Seppi Carnegie Mellon University Address correspondence to Duane Seppi, Graduate School of Industrial Administration, Carnegie Mellon University, Pittsburgh, PA 15213. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 10, Issue 1, January 1997, Pages 103–150, https://doi.org/10.1093/rfs/10.1.103 Published: 04 June 2015